Test-based learning in upper secondary school mathematics - Burman, Olle; Lundblad, Florian (My University, 2024)
This study explores the impact and experiences of test-based learning in mathe- matics education among upper secondary school students. The primary goal was to understand how test-based learning influences students’ knowledge development and their perception of this teaching method. The study compared the performance of two test-based learning groups against two control groups and collected qualitative data through surveys and interviews with both students and teachers. The results show an improvement in mathematical performance for students in the test-based learning groups compared to their counterparts in the control groups. In one of the test-based learning group, both initially high-performing and low-performing stu- dent’s improved their performance. Students in the other test-based learning group also showed improvement, particularly among the initially low-performing student’s. Surveys and interviews reveal that most students and teachers perceive test-based learning positively, emphasizing the method’s ability to identify knowledge gaps and improve memory retention. However, some students expressed concerns about stress related to frequent testing. This study concludes that test-based learning can en- hance mathematical performance, particularly among initially low-performing stu- dents’. It also highlights the importance of balancing the structure of test-based learning to minimize stress and provide challenges for high-performing students. These findings suggest that incorporating test-based learning into mathematics ed- ucation can be beneficial, provided that the tests are appropriately structured to motivate and support students at different performance levels.
Keywords: Keywords: Test-based learning, TBL, Retrieval practice, Test enhanced learning